2018
DOI: 10.1101/361709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lateral Root Priming Synergystically Arises from Root Growth and Auxin Transport Dynamics

Abstract: The root system is a major determinant of plant fitness. Its capacity to supply the plant with sufficient water and nutrients strongly depends on root system architecture, which arises from the repeated branching off of lateral roots. A critical first step in lateral root formation is priming, which prepatterns sites competent of forming a lateral root. Priming is characterized by temporal oscillations in auxin, auxin signalling and gene expression in the root meristem, which through growth become transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In this study, we demonstrated that B. amyloliquefaciens VCs significantly enhanced the signal intensity of the DR5:Luciferase expression in the OZ (Figure 3e) and subsequently formed prebranch sites in shorter period (Figure 3c). It is suggested that meristem activity can influence the oscillation frequency (Berg & Tusscher, 2018). Likewise, we observed an enhanced expression of CYCB1 in the meristematic zone of B. amyloliquefaciens…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we demonstrated that B. amyloliquefaciens VCs significantly enhanced the signal intensity of the DR5:Luciferase expression in the OZ (Figure 3e) and subsequently formed prebranch sites in shorter period (Figure 3c). It is suggested that meristem activity can influence the oscillation frequency (Berg & Tusscher, 2018). Likewise, we observed an enhanced expression of CYCB1 in the meristematic zone of B. amyloliquefaciens…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, a recent computational approach suggested that root meristem activity also influences oscillation frequency (Thea van den Berg & ten Tusscher, ). A growing meristem with constant cell division ensures the replacement velocity of cells in the elongation zone/OZ, where auxin pulses are loaded by transporters to trigger oscillations for LR formation.…”
Section: Discussionmentioning
confidence: 99%
“…DR5. DR5 (DIRECT REPEAT5) is a highly active and widespread reporter of auxin transcriptional response, which consists of 7-9 auxin response elements (AuxREs) containing tandem direct repeats of 11 base pairs that include the auxin-responsive TGTCTC element found in the soybean GH3 promoter (Ulmasov et al, 1997). These elements are crucial in the control on gene expression downstream of the TIR1/AFB-AUX/IAA-ARF signaling module.…”
Section: Spatiotemporal Regulation Of the Root Clockmentioning
confidence: 99%
“…Several DR5 reporter versions have been developed. Typically, Luciferase and GUS are transcriptionally fused under the control of the promoter described by Ulmasov et al (1997). Those constructs are herein below mentioned as DR5:Luciferase and DR5:GUS, respectively.…”
Section: Spatiotemporal Regulation Of the Root Clockmentioning
confidence: 99%